118k views
1 vote
I NEED HELP PLEASE, THANKS! :)

I NEED HELP PLEASE, THANKS! :)-example-1

2 Answers

3 votes

Answer:

Option B

Explanation:

We have tan^2( x ) + sec( x ) = 1.

First subtract 1 from either side, applying the identity tan^2( x ) = - 1 + sec^2( x ) = - 2 + sec( x ) + sec^2( x ) = 0

One key method that you should use to solve like problems, is to substitute a rather large value with a variable, such as say a. Let sec( x ) = a,

- 2 + a + a^2 = 0,

By the zero product property, a = 1, a = - 2. Substitute this value of a back into sec( x ) -

sec( x ) = 1, sec( x ) = - 2

From this we can create inequality( s ) as follows -

sec( x ) = 1, 0 ≤ x ≤ 2π, x = 0 and x = 2π

sec( x ) = - 2, 0 ≤ x ≤ 2π, x = 2π / 3 and x = 4π / 3

As you can see, x is the following solutions -

0, 2π, 2π / 3, 4π / 3

Eliminate 2π, and it should be that your solution is option B

User Funkizer
by
5.4k points
6 votes

Answer:
\bold{b)\quad (2\pi)/(3),(4\pi)/(3),0}

Explanation:

Note the following identities: tan² x = sec²x - 1


\sec x=(1)/(\cos)

tan² x + sec x = 1

(sec² x -1) + sec x = 1

sec² x + sec x - 2 = 0

(sec x + 2)(sec x - 1) = 0

sec x + 2 = 0 sec x - 1 = 0

sec x = -2 sec x = 1


(1)/(\cos x)=-2\qquad (1)/(\cos x)=1\\\\\cos x=-(1)/(2)\qquad \cos x=1\\\\x=(2\pi)/(3), (4\pi)/(3)\qquad x=0

User Dandean
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.